Validation of Computational Models of Steel-Concrete Composite Beams - PEŁKA-SAWENKO, Agnieszka; WRÓBLEWSKI, Tomasz; SZUMIGAŁA, Maciej (Engineering Transactions, 2016)
This article discusses the process of validating computational models of steel-concrete composite beams. The validation was conducted on the basis of experimental results and covers the process of modelling and identification of selected parameters in the model. During the validation process the results of experimental studies were used, and during the experimental studies the dynamic and static parameters of composite beams were assessed. The computational model and analysis were conducted for a spatial model using the finite element method in Abaqus environment. The analysis covered the elastic performance of the beams.